Design principles for addressing wicked problems through boundary crossing in higher professional education. Issue 2 (17th February 2019) - Veltman, M. E.; Van Keulen, J.; Voogt, J. M.
ABSTRACT: To an increasing extent, society requires professionals to cross boundaries in order to deal with wicked problems. However, little is known about how interventions in higher professional education (HPE) foster learning through boundary crossing in the context of addressing wicked problems. Drawing upon the three-dimension model of wickedness by Head and Akkerman and Bakker's model of the dialogical learning mechanisms of boundary crossing, this study aims to generate conjectures for design principles for the design of educational practices that will foster students' skills for addressing wicked problems through boundary crossing. This study applied a multiple case study design addressing six existing practices in HPE. The research questions were: (1) What characteristics of wicked problems are present in the selected educational practices? (2) How does the boundary crossing take place in the selected educational practices? (3) How is student learning during boundary crossing fostered in the context of dealing with the characteristics of wicked problems? Data were derived from document study, semi-structured interviews, and observations. The study conjectures that learning experiences at boundaries in the open-ended, joint effort of addressing wicked problems should be fostered and elicited by balancing and leveraging constructive tension and by making use of boundary objects and brokers.